Intra-/inter-examiner reproducibility study of gingival bleeding - Van der Weijden, G A; Timmerman, M F; Saxton, C A; Russell, J I; Huntington, E; Van der Velden, U (Journal of periodontal research, 1994)
Sulcular bleeding after stimulation with a periodontal probe has been associated with the presence of an inflammatory lesion in the gingiva. The objective of this study was to evaluate the effect of the placement of the probe in relation to the tooth surface, and the effect of standardising the probing pressure on the intra- and inter-examiner reproducibility of the gingival bleeding when using a well-defined bleeding index. Four different variations were defined: parallel bleeding index (ParBI): when the probe is run along the marginal gingiva it is held parallel to the tooth surface. Angulated bleeding index (AngBI): the probe is held at an angle of approximately 60 degrees to the longitudinal axis of the tooth and in contact with the sulcular epithelium. Controlled force parallel bleeding index (CF-ParBI)/controlled force angulated bleeding index (CF-AngBI): the same procedure as described for the ParBI and AngBI is followed, but instead of a conventional (WHO-ASH/Dentsply) probe an adjustable force probe (Brodontic-ASH/dentsply), adjusted to 0.25 N is used. The results show that the agreement both within and between clinicians could hardly be rated as 'fair' on a site basis. Approximately one in every three sites was given a different assessment on the second examination. This might have been the consequence of the repeat examination. Agreement on a quadrant basis was slightly better. Furthermore, the direction of the probing influences the number of provoked bleeding sites. Angulation of the probe produces consistently less bleeding compared with parallel placement of the probe.